Science Majoring Background Modulates the Psychological Responses to Stress on Numerical Task - Indrayanti Indrayanti; Aurelia Virgita Claudia; Satrio Priyo Adi; Galang Lufityanto (Gadjah Mada Journal of Psychology (GamaJoP), 2022)
Numerical tasks have become part of the daily activities of individuals even in academic potential tests which have the potential to cause stress to individuals. The background of majoring in science is thought to be one of the factors that influence the individual's physiological response to stress when doing numerical tasks. This study aims to investigate whether there are differences in the final results and processing stages on numerical tasks between students majoring in science and social studies. A simple mathematical numerical task was given to participants to respond by adding numbers that were close to each other within a predetermined time limit. Twenty-two participants took the test twice with a one-week gap between tests. Recording of participants' electrodermal activity while working on a task using a galvanic meter. The results show that there is no difference in performance between students in majoring in social science and science (t = 0.552; p = 0.587), however, there are indications of different stress dynamics, where students in majoring in science show a positive effect of stress, while students in majoring in social science show the opposite. Further discussed the stress response on the difference in the frequency of meetings with numerical tasks during education at school.